Diferenciação de produtos: uma análise a partir das exportações do Ceará e Pernambuco para a União Européia (2000-2011) - Nobre, Cibele de Sá Pinheiro (2013)
This study analyzed the differentiation between products of the export of Ceará and Pernambuco to the EU market during the period from 2000 to 2011. To perform this analysis were used and calculated the similarity indices, quality and variety of exports from these two states from data from the Ministry of Development, Industry and Trade. To obtain three major results. First, the similarity of patterns of Ceará and Pernambuco exports declined throughout the period analyzed. The second result was the finding that the product quality is superior to cearenses pernambucana along each year. Nevertheless, the isolated analysis of the sectors indicated that products proveinentes sectors of rubber, paper, printing, textile and clothing Pernambuco showed better quality. Finally, it was found that the Ceará exported a greater variety of products than Pernambuco throughout the period, but with a certain balance when analyzing the sectors individually.